2009
DOI: 10.1084/jem.20091386
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*35-Px–mediated acceleration of HIV-1 infection by increased inhibitory immunoregulatory impulses

Abstract: A subset of HLA-B*35 alleles, B*35-Px, are strongly associated with accelerated HIV-1 disease progression for reasons that are not understood. Interestingly, the alternative set of B*35 subtypes, B*35-PY, have no detectable impact on HIV-1 disease outcomes, even though they can present identical HIV-1 epitopes as B*35-Px molecules. Thus, the differential impact of these alleles on HIV-1 disease progression may be unrelated to interactions with HIV-1–specific CD8+ T cells. Here, we show that the B*35-Px molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 24 publications
5
88
1
1
Order By: Relevance
“…The protective effect of HLA-B*57 was also confirmed in this population, while B35 and B53 alleles were associated with poor outcome. These results are inconsistent with the previously described PX/PY theory (Huang et al, 2009) (section 7.1). Lazaryan et al (2011) found that both B*5301 (PX) and B*3501 (PY), the most frequent alleles in their groups, were equally disadvantageous.…”
Section: Susceptibility Conferred By Hla-b35 Allelescontrasting
confidence: 99%
See 2 more Smart Citations
“…The protective effect of HLA-B*57 was also confirmed in this population, while B35 and B53 alleles were associated with poor outcome. These results are inconsistent with the previously described PX/PY theory (Huang et al, 2009) (section 7.1). Lazaryan et al (2011) found that both B*5301 (PX) and B*3501 (PY), the most frequent alleles in their groups, were equally disadvantageous.…”
Section: Susceptibility Conferred By Hla-b35 Allelescontrasting
confidence: 99%
“…Differences in innate immunity could be the underlying cause: the B*35-PY molecule B*3501 and the B*35-Px molecule B*3503 differ by only one amino acid and present identical HIV-1 epitopes, yet the B*35-Px molecule binds with greater affinity to immunoglobulin-like transcript 4 (ILT4), an inhibitory MHC class I receptor expressed on DCs. This binding to ILT4 is associated with significantly stronger DC dysfunction during in vitro functional assays (Huang et al, 2009). That study concludes that differential interactions between HLA class I allele subtypes and immune regulatory MHC class I receptors on DCs is an important determinant of the immune response to the HIV virus.…”
Section: Susceptibility Conferred By Hla-b35 Allelesmentioning
confidence: 59%
See 1 more Smart Citation
“…One polymorphic residue between Eqca-N*00602 and Eqca-N*00601 was able to lead to a distinct conformation of GW12, indicating this diverse peptide presentation manner, as the peptide conformation can be changed so easily. Martin and colleagues found drastically different interactions between a self-peptide pVIPR with two HLA subtypes HLA-B*2705 and HLA-B*2709, which only differ with respect to residue 116 (Asp versus His) within the peptidebinding groove (21). The recently determined HLA-A*0301 complexed with an HIV-derived peptide RT313 also reflects the important role of residue 152 in the minor tuning of peptide side chains presented by HLA-A*0301 (Glu 152 ) and HLA-A*1101 (Ala 152 ) (59).…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenic epitope peptides recognized by virus-specific CTLs are presented by MHC (equine leukocyte Ag [ELA] in the horse and HLA in humans) molecules. The subtle changes in the peptide-binding region of MHC molecules that leads to amino acid differences have a significant impact on the immune responses to a similar peptide (21,22). It has been reported that a single amino acid polymorphism within the a2 domain of ELA can alter or even abolish recognition of Env-RW12 and another EIAV-derived CTL epitope peptide, Rev-QW11 (QAEVLQERLEW) (20).…”
mentioning
confidence: 99%